The Efficacy of Case-Based Learning Model Integrated with Critical Thinking Skills to Improve EFL Learners’ Reading Comprehension - Agustina, Lia; Ro'isatin, Umi Anis (Universitas Pendidikan Mandalika, 2024)
The CBL offer dynamic and engaging learning experiences that cater to diverse learning styles and preferences. By working collaboratively in groups, students not only enhance their language skills but also develop essential communication, teamwork, and problem-solving abilities. Therefore, this study is aimed at investigating the efficacy of case-based learning model integrated with critical thinking skills to improve EFL learners’ reading comprehension. This study is designed in a classroom action research. 27 EFL learners are involved in this study. The research participants are selected in purposive random sampling. To collect the research data, the observation sheets, reading tests, and critical thinking tests are applied as the research instruments. The data consisted of qualitative and quantitative one. Qualitative data are analyzed qualitatively while the quantitative data are counted in statistical analysis. Based on the results, the findings show that the case-based learning model integrated with critical thinking skills is effective to improve EFL learners’ reading comprehension. The improvement lies on learners’ vocabulary mastery, grammar knowledge, comprehension, reading strategies, and fluency. For further studies, researchers can include metacognitive strategies and measure learners’ linguistic awareness in learning language skills.